Clean Blood, Religion, and Moral Triage in Tuberculosis Vaccine Trials. Issue 8 (17th November 2018) - Dixon, Justin; Tameris, Michèle
ABSTRACT: During ethnographic research at a tuberculosis vaccine trial site in South Africa, trial participants often evoked the idiom of "clean blood." In this article, we illustrate how the trials enacted a form of moral triage in which "objective" bioscientific knowledge and moral subjectivity were coproduced. Participation created possibilities to demonstrate healthiness, respectability, and godliness in a context where positive self-imaginings were hard won, but could also lead to dejection and shame. We suggest that struggles to be recognized as virtuous are often overlooked in anthropological critiques of clinical trials and bioethics, but are important for understanding how trials meld with local moral worlds. Abstract :